Injury epidemiology in the first Croatian basketball league - Šola, Matilda (Array, 2021)
The aim of this study was to provide a retrospective overview of injuries during one basketball season and to analyse injury rates and potential risks among professional male and female basketball players in the First Croatian National league. A hundred and forty-two (89 males and 53 females) of 223 basketball players (64%) sustained an injury during the previous season.